The Attractiveness of the Central and Eastern European Region from the Perspective of Buyout Funds - Lang, Tomáš; Poborský, František; Dvořáčková, Anička; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
This master's thesis aims to analyze and measure the investment attractiveness of the Central and Eastern European region from the perspective of a buyout fund. The evaluation of the region's attractiveness was conducted using a selection of widely recognized factors, along with additional factors I identified as significant. Through detailed analysis, the most critical factors were selected and assessed on a scale of 1 to 5, reflecting their relevance specifically within the Central and Eastern European context. Each factor was weighted according to its perceived importance. A weighted average score was then computed from these ratings. The findings indicate that the Central and Eastern European region offers significant opportunities and potential but also poses substantial risks. Overall, its attractiveness is assessed at 78 out of 100.
Vedoucí práce: František Poborský
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: finance a oceňování podniku [obor dipl. práce]; diplomové práce; master's theses